The Effectiveness of Tutoring in Enhancing Career Maturity of 11th Grade Students - Nurwajihan Safitri; Besti Nora Dwi Putri; Yasrial Chandra (Journal of Practice Learning and Educational Development, 2026)
In this research, the background is the phenomenon of students' career maturity, who do not know their interests and talents, make mistakes in choosing their majors, and do not know the career direction they will take after graduation. Students often plan their careers unrealistically, without considering their abilities and potential. They tend to rely on others to determine their career future, due to the lack of thorough preparation in planning their next steps. The purpose of this research is to describe: 1) The depiction of students' career maturity before receiving tutoring, 2) The depiction of students' career maturity after receiving tutoring, 3) The effectiveness before and after tutoring in improving students' career maturity. This research uses an experimental method with a One Group Pretest and Posttest research design. With a population of 127 people and a sample of 50 people, the sampling technique used was purposive sampling. The instrument used is the Likert scale, while data analysis employs normality tests, homogeneity tests, and hypothesis tests.